1970
DOI: 10.5617/nordina.277
|View full text |Cite
|
Sign up to set email alerts
|

Science for life – a conceptual framework for construction and analysis of socio-scientific cases

Abstract: The aim of this paper is to describe a conceptual framework to be used as a tool for analyzing work with socio-scientific issues (SSI) and for constructing SSI cases in secondary school. The framework consists of six components describing the more detailed characteristics of SSI. The components were chosen to reflect what we know from research about what might have an impact on students' learning and interest in science. Six socio-scientific cases were then constructed and these are discussed in the article. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
0
17
0
7
Order By: Relevance
“…De acuerdo con Díaz y Jiménez-Liso (2012), «de manera más general se definen como un asunto de opinión científico y/o tecnológico en el cual existe discrepancia entre los diversos actores y fuerzas sociales que participan en el proceso ya sea por desacuerdo, discusión o debate». Como se refleja en estas definiciones y en el trabajo de autores como Kolsto (2001), Sadler (2004) y Ekborg et al (2010), estos temas se caracterizan por ser abiertos, complejos y controvertidos como resultado de la ausencia de acuerdo científico y de una respuesta única y definitiva en torno a ellos (ya que son situaciones nuevas que se sitúan en lo que se denomina ciencia frontera). Esta dimensión controvertida asociada a la mayoría de CSC es debida a diferencias sobre el contenido y la naturaleza de la ciencia (percepción del riesgo, interpretaciones de datos empíricos y teorías científicas), el impacto social de la ciencia y la tecnología (Levinson, 2006).…”
Section: Las Csc En La Educación Científicaunclassified
“…De acuerdo con Díaz y Jiménez-Liso (2012), «de manera más general se definen como un asunto de opinión científico y/o tecnológico en el cual existe discrepancia entre los diversos actores y fuerzas sociales que participan en el proceso ya sea por desacuerdo, discusión o debate». Como se refleja en estas definiciones y en el trabajo de autores como Kolsto (2001), Sadler (2004) y Ekborg et al (2010), estos temas se caracterizan por ser abiertos, complejos y controvertidos como resultado de la ausencia de acuerdo científico y de una respuesta única y definitiva en torno a ellos (ya que son situaciones nuevas que se sitúan en lo que se denomina ciencia frontera). Esta dimensión controvertida asociada a la mayoría de CSC es debida a diferencias sobre el contenido y la naturaleza de la ciencia (percepción del riesgo, interpretaciones de datos empíricos y teorías científicas), el impacto social de la ciencia y la tecnología (Levinson, 2006).…”
Section: Las Csc En La Educación Científicaunclassified
“…The above studies indicate that teacher's knowledge is of great importance to determine the effectiveness of a teacher in a science classroom (Ekborg, Ideland, & Malmberg, 2009;Bartholomew et al, 2004). From the literature, it was found that there are five main components that bring out the knowledge and practice of a teacher in teaching science using SSIs.…”
Section: Background Of the Studymentioning
confidence: 99%
“…This is because in order to address the controversial issues in science classes, it requires teachers to have a broad range of knowledge, such as economics, politics, ethics, technology, health, and environment (Ekborg et al, 2009). In addition, teachers indicate that these issues can cause conceptual difficulties to teachers and students (Hestness, McGinnis, Riedinger, & Marbach-Ad, 2011).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Real cases presented as authentic dilemmas in society instead have the potential to motivate and engage students learning socio-scientific issues (Aikenhead, 2006(Aikenhead, , 2007Oscarsson, Jidesjö, Karlsson & Strömdahl, 2009). According to Ekborg, Ideland and Malmberg (2009), school must offer students opportunities to develop skills and competence to take part in the official debate concerning authentic and contemporary challenges. To gain competence in taking informed decisions, students need training in cost-benefit analyses, judging risks, and taking a stand.…”
mentioning
confidence: 99%
“…Such students gain a higher level of commitment; rather than simply consuming knowledge, they learn how to produce knowledge. Thereby, relevant and authentic knowledge formation occurs, from a socioscientific perspective of citizenship and developed literacy (Aikenhead, 2006;Ekborg, Ideland & Malmberg, 2009). …”
mentioning
confidence: 99%